System for measuring the production CO2 in soil contaminated with soybean oil using the Arduino platform - Jorge, Emanuele Nunes de Lima Figueiredo (2017)
Carbon dioxide (CO2), also known as carbonic gas, is a gaseous chemical compound. The process of the degradation  of vegetable oil in the soil produces CO2. There are methodologies that consist in determining the rate of CO2 released by microorganisms in the process of degradation of organic compounds by chemical analysis. However, it is not easy to measure the amount of CO2 released in this degradation process. Thus, the main objective of this work was to monitor in a continuous, quantitative and efficient way, through an automated and low cost system that uses the Arduino platform the amount of CO2 produced in the degradation of vegetable oil in a contaminated soil. The results show the mean values of CO2 capture as a function of the different periods of analysis. Thus, the development of work with automated systems that aid in agricultural environments becomes extremely important for the growth in the areas of Technological Innovation.